Passive Leg Raising Maneuver and Prediction of Fluid Responsiveness: Noninvasive Monitoring of Pulse Pressure and Systolic Blood Pressure - Pickett, Joya D. (My University, 2015)
Background: Fluid boluses are administered to improve tissue hypoperfusion in shock. However, only approximately 50% of patients respond to a fluid bolus with a clinically significant increase in stroke volume index (SVI). Measurement of the response to the passive leg raising maneuver (PLRM) is an accurate method to predict fluid responsiveness using invasive and minimally invasive methods. A PLRM-induced increase in direct arterial pulse pressure (PP) ¡Ý 9% and systolic blood pressure (SBP) increase ¡Ý 9% accurately predict fluid responsiveness. Limited research has been done to evaluate non-invasive blood pressure (NIBP) response to the PLRM. Objectives: Determine if a PLRM-induced increase in PP or SBP, using oscillometric NIBP, are sensitive and specific predictors of a clinically significant increase in SVI in healthy volunteers. Methods: A repeated measures design with a convenience sample of thirty healthy volunteers was used. Hemodynamic measurements were taken pre/post PLRM, with the procedure completed twice. Bioreactance was used to measure the SVI. Results: A PLRM-induced increase in SVI of ¡Ý 15% classified 20 subjects (69%) as responders and 9 (31%) as nonresponders. In a repeat test, 15 subjects (50%) were responders, and 15 subjects (50%) were nonresponders. A PLRM-induced increase in PP ¡Ý 9% predicted fluid responsiveness with a sensitivity of 50%, specificity of 44%, similar results in the repeat test. There was no association between the PLRM-induced change in SBP and fluid responsiveness. Conclusion: The PLRM-induced change in SVI allowed for delineation of fluid responders and non-responders. However, NIBP PP and SBP were not sensitive or specific predictors of fluid responsiveness in the healthy volunteer. Key words: passive leg raising, fluid responsiveness, pulse pressure, blood pressure
Thesis (Ph.D.)--University of Washington, 2015
Keywords: Blood Pressure; Fluid Responsiveness; Passive Leg Raising; Pulse Pressure; Nursing; nursing - seattle